Descending neural drives to ankle muscles during gait and their relationships with clinical functions in patients after stroke. Issue 2 (February 2016) - Kitatani, Ryosuke; Ohata, Koji; Aga, Yumi; Mashima, Yuki; Hashiguchi, Yu; Wakida, Masanori; Maeda, Ayaka; Yamada, Shigehito
Highlights: Descending neural drive to each muscle was reduced on the paretic side during gait. Neural drive to antagonist muscles was increased during gait in stroke patients. Increased drive to antagonist muscles was related to paretic ankle muscle weakness. Abstract: Objective: The objective of this study was to investigate the descending neural drive to ankle muscles during gait in stroke patients using a coherence analysis of surface electromyographic (EMG) recordings and the relationships of the drive with clinical functions. Methods: EMG recordings of the paired tibialis anterior (TA), medial and lateral gastrocnemius (MG and LG), and TA–LG muscles were used to calculate intramuscular, synergistic, and agonist–antagonist muscle coherence, respectively, in 11 stroke patients and 9 healthy controls. Paretic motor function, sensory function, spasticity, ankle muscle strength, and gait performance were evaluated. Results: Paretic TA–TA and MG–LG beta band (15–30 Hz) coherences were significantly lower compared with the non-paretic side and controls. TA–LG beta band coherence was significantly higher on both sides compared with controls. Paretic TA–TA beta band coherence positively correlated with gait speed, and paretic TA–LG beta band coherence negatively correlated with paretic ankle plantar flexor muscle strength. Conclusions: The intramuscular and synergistic muscle neural drives were reduced during gait on the paretic side in stroke patients. The agonist–antagonist muscle neural drive was increased to compensate for paretic ankle muscle weakness. Significance: Descending neural drive reorganization to agonist–antagonist muscles is important for patients with paretic ankle muscle weakness.